2007
DOI: 10.1159/000111768
|View full text |Cite
|
Sign up to set email alerts
|

The Reproductive Tissue Specific Cystatin Subgroup of Genes: Expression during Gonadal Development in Wildtype and Testatin Knockout Animals

Abstract: Testatin has been implicated in fetal testis development due to its restricted expression in pre-Sertoli cells immediately after the onset of Sry gene expression. However, testatin knockout mice showed normal testis development and fertility. We investigated the spatial and temporal expression pattern of the Cres/testatin subgroup of genes, including the novel gene Cstl1/Cres4, in fetal mouse gonads and in adult testis, epididymis and ovary. The genes are related to the family 2 cystatins of protease inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Several new cystatin genes have been identified that differ from the classical family 2 cystatin genes. They are called the Cres/testatin subfamily and include eight mouse genes (Frygelius et al, 2007). The cystatinrelated epididymal spermatogenic protein called CRES [ID: T3-531] is a serine protease inhibitor for prohormone convertase 2 [ID: T3-532] Cornwall et al, 1992;Yuan et al, 2007).…”
Section: Microscopy Research and Techniquementioning
confidence: 99%
“…Several new cystatin genes have been identified that differ from the classical family 2 cystatin genes. They are called the Cres/testatin subfamily and include eight mouse genes (Frygelius et al, 2007). The cystatinrelated epididymal spermatogenic protein called CRES [ID: T3-531] is a serine protease inhibitor for prohormone convertase 2 [ID: T3-532] Cornwall et al, 1992;Yuan et al, 2007).…”
Section: Microscopy Research and Techniquementioning
confidence: 99%
“…In one particularly heroic experiment, the function of all three members of the insulin receptor tyrosine kinase family was eliminated before a sex‐reversed phenotype was observed 25. This and other studies52,53 expose the high level of genetic redundancy and transcriptional buffering present in the gonad transcription network at the time of sex determination, and predict that roles for many individual genes during sex determination will be masked. Yet over 50% of human disorders of sexual development (DSDs) remain unexplained by variation in known sex determination genes.…”
Section: Resultsmentioning
confidence: 92%
“…Signal peptides were predicted by Ensembl and multiple sequence alignments were performed without signal peptides via ClustalW muscle alignment (http://www.ebi.ac.uk/clustalw). Common consensus sites were indicated according to previous publications Frygelius et al 2007).…”
Section: Bioinformaticsmentioning
confidence: 99%
“…Gallus gallus (chicken) ENSGALG00000008664 located in a region on mouse chromosome 2 Frygelius et al 2007). Their orthologs in human, rhesus, rat, mouse, and cow are in synteny (Fig.…”
Section: Egg White Cystatinmentioning
confidence: 99%
See 1 more Smart Citation